The role of percutaneous tricuspid regurgitation interventions in the current clinical practice: tackling a heterogenous disease - Zach Rozenbaum; Sharon Bruoha; Azeem Latib (REC: Interventional Cardiology (English Ed.), 2022)
Severe tricuspid regurgitation (TR) is known to be independently associated with adverse prognosis.1 Its importance is further emphasized by the prevalence of this entity, particularly in the aging population.2 Until the past few years, surgical management was the only available effective treatment for isolated severe TR. Operative mortality, nonetheless, remains high.3 Moreover, surgery is associated with a 45% recurrence rate after 5 years,4 and recent data suggest that surgery may not improve the survival rate in isolated severe cases of TR.5 Accordingly, guidelines recommend TR surgery as a class 1 indication only with concomitant left-sided valvular surgery.6 Conversely, patients with prohibitive surgical risk managed conservatively were shown to have dismal outcomes.7 Fortunately, the emergence of percutaneous devices expanded the horizon of TR treatment. TACKLING THE MULTI-MECHANISTIC PATHOLOGY TR is the product of various pathophysiological mechanisms including right ventricular (RV) dilatation with consequential leaflet tethering, tricuspid annular dilatation with subsequent mal-coaptation, atrial fibrillation causing further annular dilation through atrial enlargement, and abnormalities in the tricuspid valve leaflets and apparatus. At a certain point, regurgitation itself becomes an etiology through a vicious circle of RV and atrial remodeling. Accordingly, numerous percutaneous devices are being developed for transcatheter tricuspid valve repair (TTVr) and replacement (TTVR)....